2014
DOI: 10.1155/2014/301575
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wnt Signaling in the Development of Alzheimer’s Disease: A Potential Therapeutic Target?

Abstract: Accumulating evidence supports a key role for Wnt signaling in the development of the central nervous system (CNS) during embryonic development and in the regulation of the structure and function of the adult brain. Alzheimer's disease (AD) is the most common form of senile dementia, which is characterized by β-amyloid (Aβ) deposition in specific brain regions. However, the molecular mechanism underlying AD pathology remains elusive. Dysfunctional Wnt signaling is associated with several diseases such as epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 93 publications
2
65
0
3
Order By: Relevance
“…Importantly, we demonstrated that LRP6 levels and Wnt signaling are significantly reduced in postmortem brains from late-onset AD patients. Consistent with our findings, altered expression of several Wnt signaling components has been implicated in the pathogenesis of AD (Caricasole et al, 2004; He and Shen, 2009; Wan et al, 2014). In addition, the levels of β-catenin are significantly reduced in AD individuals bearing presenilin-1 mutations (Nishimura et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, we demonstrated that LRP6 levels and Wnt signaling are significantly reduced in postmortem brains from late-onset AD patients. Consistent with our findings, altered expression of several Wnt signaling components has been implicated in the pathogenesis of AD (Caricasole et al, 2004; He and Shen, 2009; Wan et al, 2014). In addition, the levels of β-catenin are significantly reduced in AD individuals bearing presenilin-1 mutations (Nishimura et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…These functional categories are in agreement with published reports of aging and AD-specific pathways. For example, immunity is known to be involved in the pathology of AD 26 , and the Wnt signaling pathway, required for synaptic transmission and plasticity, is downregulated by β-amyloid in AD 27,28 . Also, the Aβ42 oligomers have been shown to enhance the Ras–ERK signaling pathways, inducing tau hyperphosphorylation in AD 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…These ubiquitous trans-membrane proteins have diverse biological roles in wnt signaling pathway, calcium channel regulation, cell adhesion, apoptosis, neurite outgrowth and synaptic plasticity [51, 52] (reviewed in [53]). There is now evidence that PSs may also play a role in mediating autophagy.…”
Section: Presenilins As Autophagy Modulatorsmentioning
confidence: 99%